PEMANFAATAN ATRAKTAN NABATI UNTUK PENGENDALIAN LALAT BUAH Bactrocera sp PADA TAANAMAN CABAI (Capsicum annum L.) - Yustina Maria Silvia Wonga Puu (Agriculture Faculty of Flores University, 2012)
The research aimed to know the use of vegetable attractants for monitoring fruit flies (bactrocera sp) and to know the most effective attractant on trapping fruit flies of chilli plant (Capsicum annum L). The method used in this study was Randomized Block Design namely treatment without attractan (A0), Steiner + guava attractan (A1), steiner + custard apple attractan (A2), steiner + banana attractan (A3), steiner +papaya attractan (A4). The variable is a population of fruit flies, the number of rotten fruit, and rotten intensity of fruit. The result showed that the use of vegetable attractan is effective in monitoring fruit flies pest, in which population of fruit flies pest was trapped about 27.74 %, a number of rotten fruit is 23,38 % and rotten intensity is 18,64 %. Custard apple attraction gave the highest influence on all observed variables.